Monitoring regional differences in Northwest Russia - Riitta Kosonen; Tuuli Juurikkala (European Regional Science Association (ERSA), 2003)
The paper presents the idea and results of a joint Finnish-Russian project on economic monitoring of Northwest Russia financed by the Finnish Ministry for Foreign Affairs. The regions monitored include the Murmansk region, the Karelian Republic, the Leningrad region, St.Petersburg, the Kaliningrad and the Novgorod regions. First, in the paper, the aims and operation of the monitoring project are presented. The aim is to provide regular, comprehensive and comparable information on production and demand indicators, on foreign relations, and on public sector and social developments in the regions. The bi-annual publication is the first of its kind at this detailed level. The statistical, analytical and qualitative insights are targeted at a wide international audience. Second, the development trends in the monitored regions are reviewed. It is demonstrated that the regions are gradually and slowly recovering from the economic shock caused by the breakdown of the socialist system. Also, the regions have gone through a painful and thorough restructuring, with drastic drops in production and the share of the service sector increasing. Regional differences in restructuring are pointed out. St Petersburg and the surrounding Leningrad region have become a center of food production, with the help of strong domestic demand and relatively high foreign investment flows. The development in other industries such as electronics is promising as well. Karelia and Murmansk, in turn, have been vulnerable to the world market development of their main export products, which has reflected to the general economic development of the regions. Kaliningrad region's special status shows in the importance of foreign trade and investment. Third, the paper raises the issue of uneven regional development. Northwest Russia is characterized by a rather clear North-South divide, with the Southernmost regions winning the Northern ones by virtually all indicators. In addition to economic growth and development, this difference is seen in, for example, unemployment levels and demographic trends. The paper concludes with discussing the need for qualitative research topics to highlight the actual social processes underlying the socio-economic restructuring in Northwest Russia. Also, comprehensive micro-level quantitative analysis would greatly add to the understanding of the economic processes, as to date it has mostly based on macro-level indicators.
Keywords: 330